(untitled) (REDEL. Revista Granmense de Desarrollo Local, 2019)
The present investigation approaches the necessity to assure the convenient Marketing for the commercialization of the yogurt in minidosis in the hotel entities, through its import in spite of the restrictions that exist in our legislations of the COMEX to the effect, as for the preference of the commercialization of products of the national industry and to diminish the imports. The situation is given by the insufficient national production of cow milk, matter prevails fundamental for the prosecution and production of the yogurt. On the other hand the antiquated packing systems used in the national industry are not in agreement with the presence neither the international norms of hygiene, besides their best aesthetics and possibilities of manipulation. In turn a growing demand of the product exists, of which doesn’t have the capacity of enough production the national industry.